APLIKASI SISTEM PERINGATAN TABRAKAN PADA KAPAL BERBASIS DATA GPS MENGGUNAKAN LOGIKA FUZZY - Sryang Tera Sarena; Ryan Yudha Adhitya; Catur Rakhmad Handoko; Noorman Rinanto (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2016)
Automatic Identification System (AIS)Â is an important equipment in ship for giving shipâ€™s information to other ships or harbour. Unfortunately, there is still no ship collision warning system included in AIS. Hence, an application of ship collision early warning system based on Global Positioning System (GPS) data is proposed in this paper. Here, the zero-order sugeno fuzzy logic is used to process the ships speed and position data. The output of this warning system are recommended ships speed and heading direction to prevent the ship collision based on IMO (International Maritime Organization) regulation. The object used is a ship prototype equiped with GPS. The testing is held in four position of the ship prototype againts static object. The positions are -45o, -25o, 25o dan 45o. The testing results yield 100% accuracy to the IMO regulation of the head on situations case.